THE ANALYSIS ROLE OF TRIPLE HELIX IN THE DEVELOPMENT OF HALAL INDUSTRY: STUDY ON POULTRY SLAUGHTERHOUSE IN PONOROGO DISTRICT, EAST JAVA - Dhika Amalia Kurniawan; Muhammad Ridlo Zarkasy; Abiyyi Naufal Rasyid (Jurnal Ekonomi dan Bisnis, 2025)
Indonesia, as a country with the largest Muslim population, has a high demand for poultry products that are halal and safe for consumption. This study examines the role of the triple helix (government, academics, and business actors) in developing the halal industry in Poultry Slaughterhouses (RPU) in Ponorogo Regency. The research method used a qualitative approach through focus group discussions (FGD) located at the office of the Ministry of Religious Affairs of Ponorogo involving 15 participants from various parties who have roles of responsibility and main contributions in the development of the halal RPU industry in Ponorogo. The representatives came from the Ministry of Religious Affairs of Ponorogo, the Animal Husbandry Service, the Halal Product Guarantee Agency (BPJPH), educational institutions such as Darussalam Gontor University and Muhammadiyah University of Ponorogo, and poultry slaughterhouse business actors. The FGD was carried out in a structured manner with moderator guidance to explore the role of actors in halal certification of RPU. The results of the discussion were recorded, transcribed, and analyzed using open coding techniques to identify roles, obstacles, and potential collaborations that need to be carried out in the future. The narrative results are summarized to describe the Triple Helix synergy in the development of the halal industry in Ponorogo.The results showed that the government, through the Ministry of Religious Affairs, is expected to organize structured training related to halal slaughter and certification of halal butchers. BPJPH needs to increase socialization, assistance, and funding to facilitate halal certification, as well as simplify procedures and conduct periodic audits. The Livestock Service Office is expected to be active in educating the selection of healthy poultry animals and technical assistance to fulfill the Veterinary Control Number (NKV) requirements. Poultry farmers are expected to understand the importance of halal certification and fulfill the requirements to guarantee halal products. Academics play a role in education, training, and assistance in preparing certification documents. Thus, triple helix collaboration is key in developing the halal RPU industry in Ponorogo, where each party must carry out its role according to its capabilities based on the results of the FGD evaluation.